Elevated HIV infection of CD4 T cells in MRKAd5 vaccine recipients due to CD8 T cells targeting of adapted epitopes - Qin, Kai; Boppana, Sushma; Carlson, Jonathan M.; Fiore-Gartland, Andrew; Files, Jacob; Zeng, Jie; Edberg, Jeffrey; B Mailliard, Robbie; Ochsenbauer, Christina; Bansal, Anju; Goepfert, Paul (Journal of Virology, 2021)
HIV frequently escapes CD8 T cell responses, leading to the accumulation of viral adaptations. We recently demonstrated that during chronic HIV infection, adapted epitopes can promote maturation of dendritic cells (DCs) through direct CD8 T cell interactions and lead to enhanced HIV trans-infection of CD4 T cells. Here, we sought to determine the role of such adaptations following HIV MRKAd5 vaccination. We observed that vaccine-induced adapted epitope-specific CD8 T cells promoted higher levels of DC maturation than nonadapted ones and that these matured DCs significantly enhanced HIV trans-infection. These matured DCs were associated with higher levels of interleukin 5 (IL-5) and IL-13 and a lower level of CXCL5, which have been shown to impact DC maturation, as well as a lower level of CXCL16. Finally, we observed that vaccine recipients with high HLA-I-associated adaptation became HIV infected more quickly. Our results offer another possible mechanism for enhanced infection among MRKAd5 vaccinees. Importance: Despite the well-established contribution of CD8 T cells in HIV control, prior CD8 T cell-based HIV vaccines have failed to demonstrate any efficacy in preventing viral infection. One such vaccine, known as the MRKAd5 vaccine, showed a potential increased risk of viral infection among vaccine recipients. However, the underlying mechanism(s) remains unclear. In this study, we observed that vaccine recipients with high adaptation to their HLA-I alleles were associated with an increased HIV infection risk in comparison to the others. Similar to what we observed in HIV infection in the prior study, adapted epitope-specific CD8 T cells obtained from vaccine recipients exhibit a greater capacity in facilitating viral infection by promoting dendritic cell maturation. Our findings provide a possible explanation for the enhanced viral acquisition risk among MRKAd5 vaccine recipients and highlight the importance of optimizing vaccine design with consideration of HLA-I-associated HIV adaptation.